A serial mediation model of the relationship between entrepreneurial education, orientation, motivation and intentions. Issue 2 (July 2022) - Otache, Innocent; Edopkolor, James Edomwonyi; Kadiri, Umar
Abstract: This study draws on insights from the theory of planned behaviour and social cognitive career theory to explore the impact of entrepreneurship education (EE) on undergraduate students' entrepreneurial orientation, motivation and intentions. More specifically, the objective of this study is twofold: one, to ascertain whether undergraduate students' entrepreneurial orientation, motivation and intentions would increase significantly after their exposure to EE; and two, to determine whether individual entrepreneurial orientation (IEO) and entrepreneurial motivation (EM) serially mediate the link between EE and entrepreneurial intentions (EIs). To analyse the data collected from a randomly selected sample of 217 students in three public higher education institutions, repeated-measures t -test and serial mediation analysis were performed. The results of the repeated-measures t -test indicated that the students' entrepreneurial orientation, motivation and intentions increased significantly after their exposure to EE. Likewise, the results of the serial mediation analysis showed that IEO and EM independently and serially mediated the EE-EIs relationship. The findings further clarify the EE-EIs relationship and offer some insightful implications for EE curriculum developers and governments. This study makes significant contributions to the literature on EE and EIs. Highlights: EE increases students' entrepreneurial orientation, motivation and intentions. IEO and EM are positively linked. IEO and EM independently mediate the EE-EIs relationship. IEO and EM serially mediate the EE-EIs relationship.